Broadening, Narrowing, Bifurcation, and Shift: Semantic Change Mechanisms from Proto-Austronesian to Mandailing - sha, queen; Dwi Widayati; Dardanila (Linguistik Indonesia, 2025)
This study seeks to identify and analyze semantic shifts in vocabulary from the Proto-Austronesian (PAN) language to the Mandailing language, employing a comparative historical linguistic approach. The principal data sources are a Proto-Austronesian vocabulary list and a collection of basic vocabulary obtained directly from native Mandailing speakers. The selected vocabulary items demonstrate similarities in both form and meaning. Data were collected using in-depth interviews with native Mandailing speakers to gather authentic and contextually relevant vocabulary and semantic data. Additionally, participatory observations were conducted to capture the context of vocabulary usage in everyday life that can affect changes in meaning. Data analysis was conducted through a process of data condensation, followed by the organization and presentation of the findings in descriptive narratives. Subsequently, data interpretation and conclusion drawing were carried out based on patterns and themes that emerged from the presented data. The results of the study revealed four main types of changes in meaning: broadening, narrowing, bifurcation, and shifting. This study contributes to the fields of historical linguistics and semantics, highlighting the importance of understanding meaning changes within the broader context of the linguistic and cultural evolution of the Mandailing people.